Cover Picture: Evolved Aliphatic Halogenases Enable Regiocomplementary C−H Functionalization of a Pharmaceutically Relevant Compound (Angew. Chem. Int. Ed. 51/2019). Issue 51 (28th November 2019) - Hayashi, Takahiro; Ligibel, Mathieu; Sager, Emine; Voss, Moritz; Hunziker, Jürg; Schroer, Kirsten; Snajdrova, Radka; Buller, Rebecca
Abstract : Tailored aliphatic halogenases enable the derivatization of unactivated carbon centers in non‐native substrates with exquisite stereo‐ and regioselectivity. In their Communication on page 18535, R. Buller and co‐workers report the first evolution of a non‐heme iron halogenase, WelO5*, to yield two regiocomplementary variants for the chlorination of a pharmaceutically interesting substrate. The highly evolvable nature of this enzyme underscores the usefulness of this halogenase family for late‐stage derivatization.